Citizenship Education as A Strategy to Prevent Health Hoaxes Among Nursing Students - Honest Valiant Arsana; Titis Raditia; Arya Rahmanda; Panji Maulana (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
The proliferation of health-related misinformation in the digital era underscores the strategic role of Civic Education in shaping the character and critical awareness of nursing students. Positioned at the intersection of health communication and public trust, nursing students are not only susceptible to digital misinformation but also bear the ethical responsibility of serving as credible information disseminators. This study explores the potential of Civic Education to enhance ethical reasoning, social responsibility, and critical literacy among nursing students, thereby equipping them to counter health hoaxes effectively. Employing a literature review approach, this research highlights the importance of integrating civic values such as critical thinking, digital citizenship, and moral responsibility into nursing education. The findings suggest that fostering reflective and analytical competencies within Civic Education can empower nursing students to verify information objectively, resist disinformation, and act as agents of change in cultivating a health-literate and hoax-resilient society. The internalization of civic values is thus a crucial foundation for developing health professionals who are not only technically proficient but also socially accountable and ethically grounded.